The Perception of Tourism Development in a Less Developed Region-Mardin Sample - Elif Gunduz; Rahmi Erdem (European Regional Science Association (ERSA), 2010)
Tourism is one of the most dynamic and fastest growing global industries and its growth is necessarily beneficial because it will contribute to economic development in heritage places. But it is clear that heritage places are fragile and vulnerable to tourism if not managed. Managing tourism can have substantial inherent potential to underpin sustainable development and conservation. So, for tourism planning in developing regions to be effective and responsive to community interests, there needs to be a coordinated system of planning. For planners, the principal goal is to create a strategy for minimising the adverse impacts and maximising gains from tourism. This would have to include the management of the cultural resource and the quality of new development, the uses and activities the built environment sustains, and the integration of both these factors with the sociocultural needs of the local community. Mardin is a candidate city for the World Heritage Sites List with its stone architecture and unique religious and traditional buildings in Türkiye. The city is defined as "cultural landscape area" with its medieval view. It appeals to be as one of the most attractive cities that has unique cultural heritage and socio-cultural aspects. Tourism has been considered as a main component in order to enliven the city's economy especially in recent years. To sustain the tool illustrated above, the local' view towards tourism and tourists needs to be measured. The aim of this paper is to measure the local's attitudes towards tourism and economic development relations in a less developed region. The study is focussed on findings about socio-demographic analyses and perception of local people's view towards tourism. Development of the study involved a staged process of survey, analysis and assessment which included public consultation.
Keywords: 330; Tourism; Local People; Less Developed Region; Tourism Perception; Economic Development; Mardin